Survey of Present Practices in Recognizing Revenues, Expenses, Gains, and Losses (Book). - Meyer, Philip E.; Windal, Floyd W. (The Accounting Review, 1982)
Reviews the book "Survey of Present Practices in Recognizing Revenues, Expenses, Gains, and Losses," by Henry R. Jaenicke.